Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Coxiella burnetii shedding in dairy cattle and its correlation with humoral and cell-mediated immune responses - Lucy O’Shannessy; John K. House; Bridgette G. Logan; John M. Morton; Sam Rowe; Paul A. Sheehy; Benjamin U. Bauer; Katrina L. Bosward (Veterinary Microbiology, 2026)

Pink Cricket Club: Dramatic color change in a Neotropical leaf‐masquerading katydid ( Arota festae , Griffini, 1896) - J. Benito Wainwright; Zeke W. Rowe; Matthew P. Greenwell; Patrick G. Cannon; Nathan W. Bailey; Graeme D. Ruxton (Ecology, 2026)

Integrating technology and environmental data to predict mismanaged plastic waste in a watershed - Lara M. Pinheiro; Diana Ita‐Nagy; Desireé G. Hidalgo; Daniela Flor; Andrea Osorio Baquero; Nicole Becerra; Inty Grønneberg; Ian Vázquez‐Rowe; Ramzy Kahhat; Ceri Lewis; Tamara S. Galloway (Journal of Industrial Ecology, 2025)
Comprehensive methods for estimating mismanaged waste accumulation in the environment are limited, especially in the Global South, and new technologies are urgently needed. Here, we applied the Azure system, a physical floating barrier designed to retain and extract river floating waste while providing observational data of mismanaged waste, comparing results with a modeling tool that uses material flow analysis to provide estimates of mismanaged waste, incorporating environmental and socioeconomic factors. The Azure system was installed at the Portoviejo River (Ecuador), and anthropogenic litter was removed, extracted, weighed, and classified. Approximately 13.8 tonnes (t) of litter were collected over 2 years of sampling, of which 87% were plastic bags containing domestic waste. About 45% of the total waste collected, that is, 6.2 t, was estimated to be plastic waste. In contrast, modeled mismanaged plastic waste estimates for the Portoviejo River varied between 148 and 1858 t per year, at least two orders of magnitude higher than field data. These results highlight the discrepancy that can occur between observational data and waste estimates. The factors that contribute to this are discussed here to help understand riverine waste sources and transport to the ocean. The results emphasize the need for a better understanding of socioeconomic and environmental aspects in the Global South to help the development of better modeling tools. Our findings of domestic deposition as a major source of riverine contamination in the Portoviejo watershed emphasize the importance of waste management for tackling river contamination. Effective monitoring tools, such as the Azure system, could help improve this.

Comparison of country-specific predictions of feed intake and methane emissions in sheep using different proxies - Q. Le Graverand; N. Lambe; F. McGovern; E.A. Navajas; P. Johnson; N. McHugh; I. De Barbieri; G. Ciappesoni; S. Rowe; B.A. Åby; J. Conington; C. Marie-Etancelin; et al. (Livestock Science, 2025)

Mudstone diagenesis in the Cenomanian–Turonian Eagle Ford Group in the San Marcos Arch area. PART I: Chemostratigraphy, early diagenesis, bitumen expulsion and migration pathways - Lucy T. Ko; Robert G. Loucks; Harry Rowe; Robert M. Reed; J. Evan Sivil; Rieko Adriaens (Marine and Petroleum Geology, 2025)

Corrigendum to ‘Mudstone diagenesis with depth and thermal maturity in the Cenomanian–Turonian Eagle Ford Group. PART II: Diagenetic processes and paragenetic sequence’ [Mar. Petrol. Geol. 170 (2024) 107085 1–39] - Lucy T. Ko; Robert G. Loucks; Harry Rowe; Rieko Adriaens; J. Evan Sivil; Gilles Mertens (Marine and Petroleum Geology, 2024)

Mudstone diagenesis with depth and thermal maturity in the Cenomanian–Turonian Eagle Ford group. PART II: Diagenetic processes and paragenetic sequence - Lucy T. Ko; Robert G. Loucks; Harry Rowe; Rieko Adriaens; J. Evan Sivil; Gilles Mertens (Marine and Petroleum Geology, 2024)

C9orf72-Associated Dipeptide Repeat Expansions Perturb ER-Golgi Vesicular Trafficking, Inducing Golgi Fragmentation and ER Stress, in ALS/FTD - Jessica Sultana; Audrey M. G. Ragagnin; Sonam Parakh; Sayanthooran Saravanabavan; Kai Ying Soo; Marta Vidal; Cyril Jones Jagaraj; Kunjie Ding; Sharlynn Wu; Sina Shadfar; Emily K. Don; Anand Deva; et al. (Molecular Neurobiology, 2024)
Hexanucleotide repeat expansions (HREs) in the chromosome 9 open reading frame 72 ( C9orf72 ) gene are the most frequent genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Both are debilitating neurodegenerative conditions affecting either motor neurons (ALS) in the brain and spinal cord or neurons in the frontal and/or temporal cortical lobes (FTD). HREs undergo repeat-associated non-ATG (RAN) translation on both sense and anti-sense strands, generating five distinct dipeptide repeat proteins (DPRs), poly-GA, -GR, -GP, -PA and -PR. Perturbed proteostasis is well-recognised in ALS pathogenesis, including processes affecting the endoplasmic reticulum (ER) and Golgi compartments. However, these mechanisms have not been well characterised for C9orf72-mediated ALS/FTD. In this study we demonstrate that C9orf72 DPRs polyGA, polyGR and polyGP (× 40 repeats) disrupt secretory protein transport from the ER to the Golgi apparatus in neuronal cells. Consistent with this finding, these DPRs also induce fragmentation of the Golgi apparatus, activate ER stress, and inhibit the formation of the omegasome, the precursor of the autophagosome that originates from ER membranes. We also demonstrate Golgi fragmentation in cells undergoing RAN translation that express polyGP. Furthermore, dysregulated ER-Golgi transport was confirmed in C9orf72 patient dermal fibroblasts. Evidence of aberrant ER-derived vesicles in spinal cord motor neurons from C9orf72 ALS patients compared to controls was also obtained. These data thus confirm that ER proteostasis and ER-Golgi transport is perturbed in C9orf72-ALS in the absence of protein over-expression. Hence this study identifies novel molecular mechanisms associated with the ER and Golgi compartments induced by the C9orf72 HRE.

Uncovering the hidden world of riverbed sediments: The role of sediment heterogeneity and cross-bar channel fills in the hydrogeochemical dynamics of the hyporheic zone - Jeffery T. McGarr; Pei Li; Robert G. Ford; Teagan Kleman; Colton Fields; Julie Hobbs; Lydia Lupton; Emma Poston; Thomas Marsh; Leah Trutschel; Ken M. Fritz; Annette Rowe; et al. (Journal of Hydrology, 2024)

Can the cross-education of strength attenuate the impact of detraining after a period of strength training? A quasi-randomized trial - Grant S. Rowe; Anthony J. Blazevich; Janet L. Taylor; Timothy Pulverenti; G. Gregory Haff (European Journal of Applied Physiology, 2024)
Purpose Unilateral strength training may attenuate the decline in muscle strength and size in homologous, contralateral muscles. This study aimed to determine whether the cross-education of strength could specifically attenuate the effects of detraining immediately after a short (prehabilitation-type) period of strength training. Methods Twenty-six strength-trained participants were assigned to either four weeks of unilateral strength training of the stronger arm (UNI) or detraining (Detrain). Motor evoked potential (MEP) and cortical silent period (cSP) responses, muscle cross-sectional area (CSA Flexor ; peripheral quantitative computed tomography) and maximal strength, rate of force development (RFD) and muscle activation (EMG) were examined in both elbow flexors before and after the intervention period. Results In UNI, one-repetition maximum (1-RM) strength improved in both the trained (∆ = 2.0 ± 0.9 kg) and non-trained (∆ = 0.8 ± 0.9 kg) arms despite cessation of training of the weaker arm, whereas 1-RM strength was unchanged in Detrain. Maximal voluntary isometric contraction, isokinetic peak torque, and RFD did not change in either group. No neural changes were detected in UNI, but cSP increased in Detrain (∆ = 0.010 ± 0.015 s). CSA Flexor increased in the trained arm (∆ = 51 ± 43 mm 2 ) but decreased in the non-trained arm (∆ = -53 ± 50 mm 2 ) in UNI. CSA Flexor decreased in both arms in Detrain and at a similar rate to the non-trained arm in UNI. Conclusion UNI attenuated the effects of detraining in the weaker arm as shown by the improvement in 1-RM strength. However, the cross-education of strength did not attenuate the decline in muscle size in the contralateral arm.

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

Speciation across biomes: Rapid diversification with reproductive isolation in the Australian delicate mice - Emily Roycroft; Fred Ford; Till Ramm; Rhiannon Schembri; William G. Breed; Phoebe A. Burns; Kevin C. Rowe; Craig Moritz (Molecular Ecology, 2024)
Phylogeographic studies of continental clades, especially when combined with palaeoclimate modelling, provide powerful insight into how environment drives speciation across climatic contexts. Australia, a continent characterized by disparate modern biomes and dynamic climate change, provides diverse opportunity to reconstruct the impact of past and present environments on diversification. Here, we use genomic‐scale data (1310 exons and whole mitogenomes from 111 samples) to investigate Pleistocene diversification, cryptic diversity, and secondary contact in the Australian delicate mice (Hydromyini: Pseudomys ), a recent radiation spanning almost all Australian environments. Across northern Australia, we find no evidence for introgression between cryptic lineages within Pseudomys delicatulus sensu lato, with palaeoclimate models supporting contraction and expansion of suitable habitat since the last glacial maximum. Despite multiple contact zones, we also find little evidence of introgression at a continental scale, with the exception of a potential hybrid zone in the mesic biome. In the arid zone, combined insights from genetic data and palaeomodels support a recent expansion in the arid specialist P. hermannsburgensis and contraction in the semi‐arid P. bolami . In the face of repeated secondary contact, differences in sperm morphology and chromosomal rearrangements are potential mechanisms that maintain species boundaries in these recently diverged species. Additionally, we describe the western delicate mouse as a new species and recommend taxonomic reinstatement of the eastern delicate mouse. Overall, we show that speciation in an evolutionarily young and widespread clade has been driven by environmental change, and potentially maintained by divergence in reproductive morphology and chromosome rearrangements.

In vitro permeation of nicotine and tobacco specific nitrosamines from smokeless tobacco product extracts in a 3D buccal tissue model - Brian M. Keyser; Hannah Flockton; Randy A. Weidman; Rebecca Payne; Jannell Rowe; Kristen G. Jordan (Toxicology Letters, 2024)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

The implementation of a national paediatric oncology protocol for neuroblastoma in South Africa - Jaques van Heerden; Marc Hendricks; Janet Poole; Ané Büchner; Gita Naidu; Jan du Plessis; Barry van Emmenes; Anel van Zyl; Ronelle Uys; Johani Johani; G. P. Hadley; Derek Harrison; et al. (Cancer Causes & Control, 2021)

Correction to: Beyond big versus small: assessing spatial variation of urban neighborhood block structures in high-density cities - ChengHe Guan; Peter G. Rowe (Socio-Ecological Practice Research, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Beyond big versus small: assessing spatial variation of urban neighborhood block structures in high-density cities - ChengHe Guan; Peter G. Rowe (Socio-Ecological Practice Research, 2021)

Long-term decline in the parasitism rate of passionvine hopper eggs (Scolypopa australis) - D. P. Logan; C. A. Rowe; P. G. Connolly (BioControl, 2020)

Temperature influences on growth of unfished juvenile Northern cod ( Gadus morhua ) during stock collapse - Darrell R. J. Mullowney; George A. Rose; Earl G. Dawe; Sherrylynn Rowe; Gary L. Maillet; Eric J. Pedersen (Fisheries Oceanography, 2019)
This study examined growth of unfished juvenile Northern cod ( Gadus morhua ) off Newfoundland concomitant with stock collapse in the cold early 1990s. Two unpublished data sets were examined, one from collapse‐period trapping sites along the northeast coast of Newfoundland and one from a post‐collapse inshore trawl survey. Cumulative surface and bottom temperatures were significant predictors of growth rates of the young fish with year‐classes born during collapse experiencing slower growth than those born during subsequent warming. Relationships between accrued temperature and growth were consistent across periods, with slow growth of collapse‐period fish reflecting slower accumulation of temperature‐at‐age. Temperature influences were spatially broad‐based with no significant differences in growth rates for fish captured along the entire northeast coast of Newfoundland. Predicted differences in growth rates for collapse versus recovery year‐classes were proportional to cumulative surface temperatures but not cumulative bottom temperatures. Although significant, temperature effects on growth were relatively unimportant at youngest ages. Overall, growth differences between periods were small but large differences occurred between slowest and fastest growing year‐classes. The results suggest initial responses to increasing temperatures were delayed following collapse. We conclude that although temperature was an important determinant of dampened productivity that it alone cannot account for the collapse and slow recovery of the stock. This is the first known study to directly quantitatively link temperature impacts to an unfished component of the Northern cod stock complex during collapse, removing need for implicit assumptions about whether or not cold conditions contributed to the collapse of this iconic fish stock.

Sources of primary production to Arctic bivalves identified using amino acid stable carbon isotope fingerprinting - Audrey G. Rowe; Katrin Iken; Arny L. Blanchard; Diane M. O'Brien; Renate Døving Osvik; Martina Uradnikova; Matthew J. Wooller (Isotopes in Environmental and Health Studies, 2019)

Liver and muscle glycogen oxidation and performance with dose variation of glucose–fructose ingestion during prolonged (3 h) exercise - Andy J. King; John P. O’Hara; Nicola C. Arjomandkhah; Josh Rowe; Douglas J. Morrison; Thomas Preston; Roderick F. G. J. King (European Journal of Applied Physiology, 2019)

Gait stability in response to platform, belt, and sensory perturbations in young and older adults - S. Roeles; P. J. Rowe; S. M. Bruijn; C. R. Childs; G. D. Tarfali; F. Steenbrink; M. Pijnappels (Medical & Biological Engineering & Computing, 2018)

Towards improved practices in Life Cycle Assessment of seafood and other aquatic products - Angel Avadí; Patrik J. G. Henriksson; Ian Vázquez-Rowe; Friederike Ziegler (The International Journal of Life Cycle Assessment, 2018)

Influence of porosity and groundmass crystallinity on dome rock strength: a case study from Mt. Taranaki, New Zealand - Edgar U. Zorn; Michael C. Rowe; Shane J. Cronin; Amy G. Ryan; Lori A. Kennedy; James K. Russell (Bulletin of Volcanology, 2018)

Application of novel analytical ultracentrifuge analysis to solutions of fungal mannans - Richard B. Gillis; Gary G. Adams; David T. M. Besong; Eva Machová; Anna Ebringerová; Arthur J. Rowe; Stephen E. Harding; Trushar R. Patel (European Biophysics Journal, 2017)

Risk/Benefit Communication about Food—A Systematic Review of the Literature - L. J. Frewer; A. R. H. Fischer; M. Brennan; D. Bánáti; R. Lion; R. M. Meertens; G. Rowe; M. Siegrist; W. Verbeke; C. M. J. L. Vereijken (Critical Reviews in Food Science and Nutrition, 2016)

Empirical realised niche models for British coastal plant species - Susan G. Jarvis; Edwin C. Rowe; Peter A. Henrys; Simon M. Smart; Laurence Jones; Angus Garbutt (Journal of Coastal Conservation, 2016)

Cities are hotspots for threatened species - Christopher D. Ives; Pia E. Lentini; Caragh G. Threlfall; Karen Ikin; Danielle F. Shanahan; Georgia E. Garrard; Sarah A. Bekessy; Richard A. Fuller; Laura Mumaw; Laura Rayner; Ross Rowe; Leonie E. Valentine; et al. (Global Ecology and Biogeography, 2016)
Aim Although urbanization impacts many species, there is little information on the patterns of occurrences of threatened species in urban relative to non‐urban areas. By assessing the extent of the distribution of threatened species across all A ustralian cities, we aim to investigate the currently under‐utilized opportunity that cities present for national biodiversity conservation. Location A ustralian mainland, T asmania and offshore islands. Methods Distributions of A ustralia's 1643 legally protected terrestrial species (hereafter ‘threatened species’) were compiled. We assessed the extent to which they overlapped with 99 cities (of more than 10,000 people), with all non‐urban areas, and with simulated ‘dummy’ cities which covered the same area and bioregion as the true cities but were non‐urban. We analysed differences between animals and plants, and examined variability within these groups using species accumulation modelling. Threatened species richness of true versus dummy cities was analysed using generalized linear mixed‐effects models. Results A ustralian cities support substantially more nationally threatened animal and plant species than all other non‐urban areas on a unit‐area basis. Thirty per cent of threatened species were found to occur in cities. Distribution patterns differed between plants and animals: individual threatened plant species were generally found in fewer cities than threatened animal species, yet plants were more likely to have a greater proportion of their distribution in urban areas than animals. Individual cities tended to contain unique suites of threatened species, especially threatened plants. The analysis of true versus dummy cities demonstrated that, even after accounting for factors such as net primary productivity and distance to the coast, cities still consistently supported a greater number of threatened species. Main conclusions This research highlights that A ustralian cities are important for the conservation of threatened species, and that the species assemblages of individual cities are relatively distinct. National conservation policy should recognize that cities play an integral role when planning for and managing threatened species.

Groundmass crystallisation and cooling rates of lava-like ignimbrites: the Grey’s Landing ignimbrite, southern Idaho, USA - B. S. Ellis; B. Cordonnier; M. C. Rowe; D. Szymanowski; O. Bachmann; G. D. M. Andrews (Bulletin of Volcanology, 2015)

Terrestrial runoff may reduce microbenthic net community productivity by increasing turbidity: a Mediterranean coastal lagoon mesocosm experiment - A. Liess; C. Faithfull; B. Reichstein; O. Rowe; J. Guo; R. Pete; G. Thomsson; W. Uszko; S. N. Francoeur (Hydrobiologia, 2015)

MultiSig: a new high-precision approach to the analysis of complex biomolecular systems - Richard B. Gillis; Gary G. Adams; Thomas Heinze; Melanie Nikolajski; Stephen E. Harding; Arthur J. Rowe (European Biophysics Journal, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

High rate of prey consumption in a small predatory fish on coral reefs - W. E. Feeney; O. M. Lönnstedt; Y. Bosiger; J. Martin; G. P. Jones; R. J. Rowe; M. I. McCormick (Coral Reefs, 2012)

Impacts of atmospheric nitrogen deposition: responses of multiple plant and soil parameters across contrasting ecosystems in long‐term field experiments - Gareth K. Phoenix; Bridget A. Emmett; Andrea J. Britton; Simon J. M. Caporn; Nancy B. Dise; Rachel Helliwell; Laurence Jones; Jonathan R. Leake; Ian D. Leith; Lucy J. Sheppard; Alwyn Sowerby; Michael G. Pilkington; et al. (Global Change Biology, 2012)
Atmospheric nitrogen ( N ) deposition is a global and increasing threat to biodiversity and ecosystem function. Much of our current understanding of N deposition impacts comes from field manipulation studies, although interpretation may need caution where simulations of N deposition (in terms of dose, application rate and N form) have limited realism. Here, we review responses to simulated N deposition from the UKREATE network, a group of nine experimental sites across the UK in a diversity of heathland, grassland, bog and dune ecosystems which include studies with a high level of realism and where many are also the longest running globally on their ecosystem type. Clear responses were seen across the sites with the greatest sensitivity shown in cover and species richness of bryophytes and lichens. Productivity was also increased at sites where N was the limiting nutrient, while flowering also showed high sensitivity, with increases and declines seen in dominant shrub and forb species, respectively. Critically, these parameters were responsive to some of the lowest additional loadings of N (7.7–10 kg ha −1 yr −1 ) showing potential for impacts by deposition rates seen in even remote and ‘unpolluted’ regions of E urope. Other parameters were less sensitive, but nevertheless showed response to higher doses. These included increases in soil % N and ‘plant available’ KCl extractable N , N cycling rates and acid–base status. Furthermore, an analysis of accumulated dose that quantified response against the total N input over time suggested that N impacts can ‘build up’ within an ecosystem such that even relatively low N deposition rates can result in ecological responses if continued for long enough. Given the responses have important implications for ecosystem structure, function, and recovery from N loading, the clear evidence for impacts at relatively low N deposition rates across a wide range of habitats is of considerable concern.

Structure and heterogeneity of gliadin: a hydrodynamic evaluation - Shirley Ang; Jana Kogulanathan; Gordon A. Morris; M. Samil Kök; Peter R. Shewry; Arthur S. Tatham; Gary G. Adams; Arthur J. Rowe; Stephen E. Harding (European Biophysics Journal, 2010)

Galantamine-induced improvements in cognitive function are not related to alterations in α4β2 nicotinic receptors in early Alzheimer’s disease as measured in vivo by 2-[18F]Fluoro-A-85380 PET - J. R. Ellis; P. J. Nathan; V. L. Villemagne; R. S. Mulligan; T. Saunder; K. Young; C. L. Smith; J. Welch; M. Woodward; K. A. Wesnes; G. Savage; C. C. Rowe (Psychopharmacology, 2009)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Defining population boundaries: use of three Bayesian approaches with microsatellite data from British natterjack toads ( Bufo calamita ) - G. ROWE; T. J. C. BEEBEE (Molecular Ecology, 2007)
Defining boundaries between populations is often difficult in the absence of information about current levels of gene flow. Such definitions can be important, however, both for the understanding of population dynamics and for conservation planning. Recently developed Bayesian methods for analysing genetic data now provide a powerful approach to this problem. Natterjack toads Bufo calamita are endangered in Britain, where their distribution is restricted to four geographically discrete regions. In three of these regions the boundaries between populations are often uncertain. We therefore used Bayesian approaches with microsatellite data to try and define British natterjack population structure, and thus inform conservation management. A large sample of natterjack toads from all 38 locations in Britain where the species is native was genotyped at eight microsatellite loci. The genetic diversity of natterjack populations declined as a function of increasing latitude, echoing postglacial colonization dynamics. Comparisons of three assignment methods ( structure , baps and geneland ) generated some broad similarities but also some inconsistencies in the definitions of population structure, especially in the most complex region (south Cumbria). Implications of the analyses for the future conservation of Bufo calamita in Britain are discussed.

Defining population boundaries: use of three Bayesian approaches with microsatellite data from British natterjack toads (Bufo calamita) - G. ROWE; T. J. C. BEEBEE (Molecular Ecology, 2007)

Phylogenetic relationships of dengue-1 viruses from Argentina and Paraguay - G. Avilés; J. Rowe; J. Meissner; J. C. Manzur Caffarena; D. Enria; S. St. Jeor (Archives of Virology, 2002)

Implications of heterogeneity on procedures for estimating plant 15N recovery in hedgerow intercrop systems - E. C. Rowe; G. Cadisch (Agroforestry Systems, 2002)

Considerations on the use of video playbacks as visual stimuli: the Lisbon workshop consensus - R. F. Oliveira; G. G. Rosenthal; I. Schlupp; P. K. McGregor; I. C. Cuthill; J. A. Endler; L. J. Fleishman; J. Zeil; E. Barata; F. Burford; D. Gonçalves; M. Haley; et al. (acta ethologica, 2000)

Monitoring an Experimental Soil Waste Near London, Ontario, Canada - E.K. Yanful; P.H. Simms; R.K. Rowe; G. Stratford (Geotechnical and Geological Engineering, 1999)

Acute and Genotoxic Effects of Baku Harbor Sediment on Russian Sturgeon, Acipenser guildensteidti - J. W. Bickham; G. T. Rowe; G. Palatnikov; A. Mekhtiev; M. Mekhtiev; R. Y. Kasimov; D. W. Hauschultz; J. K. Wickliffe; W. J. Rogers (Bulletin of Environmental Contamination and Toxicology, 1998)

Testing the safety-net role of hedgerow tree roots by 15N placement at different soil depths - E. C. Rowe; K. Hairiah; K. E. Giller; M. Van Noordwijk; G. Cadisch (Agroforestry Systems, 1998)

Archive Contributions to a Molecular Phylogeography of the Toad Bufo calamita in Britain - T. J. C. Beebee; G. Rowe; T. Burke (Biochemical Genetics, 1998)

Phylogeography of the natterjack toad Bufo calamita in Britain: genetic differentiation of native and translocated populations - G. ROWE; T. J. C. BEEBEE; T. BURKE (Molecular Ecology, 1998)
The natterjack toad Bufo calamita is rare in Britain, which is at the northwestern edge of its biogeographical range. We investigated the level of genetic differentiation amongst almost all (34 out of 38) of the surviving British populations of this species, and among six new populations established by translocations during the 1980s. For eight microsatellite loci, allele sizes and frequencies were analysed using samples from each of these populations. The populations clustered into three robustly differentiated groups, each of which corresponded with a geographical region (east/southeast England, Merseyside and Cumbria). The Cumbrian populations showed a further weak geographical substructuring into northern and southern clades. The populations in south Cumbria were genetically more diverse than those in any of the other regions, as judged by the mean numbers of alleles per locus and the mean heterozygosity estimates. The translocated populations clustered close to their founders and, with one exception, did not differ significantly with respect to mean allele numbers, heterozygosity or polymorphism level. However, significant genetic differentiation (as measured by unbiased R ST ) was found between all but one of the founder‐translocation pairs. The implications of this phylogeographic study for the future conservation of B. calamita in Britain are discussed.

Further analysis of the role of spectrin repeat motifs in α-actinin dimer formation - G. Flood; A. J. Rowe; D. R. Critchley; W. B. Gratzer (European Biophysics Journal, 1997)

PCR primers for polymorphic microsatellite loci in the anuran amphibian Bufo calamita - G. Rowe; T. J. C. Beebee; T. Burke (Molecular Ecology, 1997)

Analysis of the causal components of assortative mating in water striders - L. Rowe; G. Arnqvist (Behavioral Ecology and Sociobiology, 1996)

Chromatographic studies on the origin of the cultivated diploid potatosolanum × ajanhuiri juz. et buk - Z. Huamán; J. G. Hawkes; P. R. Rowe (American Journal of Potato Research, 1983)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

s 59th annual meeting Potato Association of America - D. E. Hudson; M. D. Volz; B. B. DePhillips; Gene A. Mathia; Frank Haynes; N. A. Wynn; Allen E. Abrahams; Lewis A. Schaper; Paul H. Orr; Earl C. Yaeger; Combs Joseph; Robert L. Mercer; et al. (American Journal of Potato Research, 1975)